Microscopic analysis and histochemical observations of the medicinal root of lostephane heterophylla (Cav.) Benth. ex Hemsl. (Asteraceae) - Sandoval, E.=700 1 Bye, R.A.; Rios, G.
(Es, En)
Ilus., 32 ref
Keywords: ASTERACEAE; ANALISIS DE TEJIDOS; RAICES; COMPOSICION QUIMICA; MEDICAMENTOS; MEXICO